Design and Realization of Labriform Mode Swimming Robot Based on Concave Pectoral Fins - Naser, Farah Abbas; Rashid, Mofeed Turky (Journal of Applied Nonlinear Dynamics, 2026)
A Swimming performance underlies the biomechanical properties and functional morphology of fish fins. In this article, design and realization of a swimming robot propelled by a pair of pectoral fin is implemented. The suggested shape of the pectoral fins is concave; this type of fin provides a simple approach in generating effective hydrodynamic thrust force through only one degree of freedom (1-DOF). Next, we show the effect of varying fin oscillation speed in two phases, the first phase is the power stroke one, where the fins start to push toward the backward of the body, and the recovery phase, where the fins return toward the frontal part of the body. The detailed steps of the robot design are presented and the thrust force exerted by pectoral fins has been evaluated. The robot is consisting of a rigid-body with an elliptical cross-sectional area, which helps in minimizing the water resistance during the thrusting process. Since pectoral fins provide a vital role in the propulsion mechanism of Labridae fish, the proposed model is driven by a pair of concave-shaped fin to simulate labriform mode swimming mechanism. For motion control, we have suggested to use PID controller in order to improve the system performance. The kinematic and dynamic model of a swimming robot has been derived based on Newton-Euler equations, while an evaluation of the total hydrodynamic forces that are exerted on the swimming robot’s body is studied via the computational fluid dynamics (CFD) method. The proposed design has been validated theoretically via Solidworks® platform and examined experimentally. The results of the simulation and practical experiments showed the validity and agility of Labriform swimming robot.